Characterization of the morphology, structure and wettability of phase dependent lamellar and nanotube oxides on anodized Ti-10Nb alloy - Luz, Aline R.; Santos, Luciane S.; Lepienski, Carlos M.; Kuroda, Pedro B. [UNESP]; Kuromoto, Neide K. (Elsevier B.V., 2018)
Nanotubes grown on Ti and its alloys have been extensively investigated for the biomaterials applications, since these structures improve the surface biocompatibility and the corrosion resistance due to oxide formation. Some researchers showed that the microstructure of the pure Ti affect the morphology of nanotubes grown by anodic process. However, this subject is rarely investigated for nanotubes grown on Ti alloys. In the same way, nanostructured films formed by concomitant regions of tubes and lamellar structures hardly ever were reported. Investigations concerning these topics are required once beta titanium alloys are suitable candidates to replace the pure Ti and Ti-Al-V alloys for biomedical applications. Beta alloys composed of non-toxic elements (Nb, Ta, Mo) are biocompatible and have an excellent mechanical properties and corrosion resistance. The present work investigated questions regarding to the effect of microstructure of Ti-10Nb alloy on morphology of nanostructured film growth by anodization. The morphology, thickness, composition and atomic arrangement (amorphous/crystalline) of formed oxides, and the contact angle of anodic film were investigated. The X-ray diffraction patterns and SEM image show that the Ti-10Nb alloy is composed by alpha (hcp) and beta (bcc) phases. SEM and TEM techniques revel that self-organized nanotubes grew on alpha phase, whereas a lamellar structure with transversal holes grew on beta-phase. Crystalline oxides are formed at oxide-metal interface, as indicated by X-ray diffraction patterns. However, the tubes and lamellas grown over the compact oxide are amorphous, as-prepared and annealed at 230 degrees C for 3 h, as showed by SAED patterns. The nanostructured films annealed at 430 degrees C and at 530 degrees C were damaged. A few changes were observed in XRD patterns of film annealed at 230 degrees C while the morphology held similar as the unannealed film. Finally, the presence of phosphorus ions incorporated into the anodic layer makes the surface hydrophilic, since a similar nanostructured film without phosphorous incorporation results hydrophobic. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Alpha-beta alloy; Ti-10Nb alloy; Nanotubes; Lamellar structure; Phosphorus incorporation; Wettability